Design of an eight-hole directional coupler for W-band cryogenic receivers - Yan, Zhuoying; Zhong, Weiye; Ma, Jia; Zhang, Hui; Zhang, Chao; Pu, Zhengwei; Wang, Junzhi (Frontiers in Astronomy and Space Sciences, 2025)
For the system noise temperature calibration of the K/Q/W triple-band cryogenic receiver on Tianma Radio Telescope (TMRT), a design of W-band eight-hole waveguide directional coupler is proposed in this paper. Based on the hole coupling principle proposed by Gian Guido Gentili, a simulation model of the eight-hole coupler is designed by ANSYS HFSS. Both simulation and experimental results demonstrate that the coupler exhibits excellent performance across the 80–110 GHz, with a coupling coefficient ranging from −25 dB to −26 dB, a directivity greater than 11 dB, and an isolation below −38 dB.